(untitled) (Research, Society and Development, 2023)
Introduction: The search for agility in routine procedures in the dental clinic environment has triggered the development of new dental materials, including bulk fill composite resins which, among other properties, have reduced polymerization shrinkage when compared to conventional composite resins. Objective: To observe the polymerization shrinkage of bulk-fill resin when applied in increments between 4 - 5 mm thick, compared to conventional composite resins (2 mm increments). Methodology: This is an integrative review, where articles from the Virtual Health Library (VHL), Scientific Electronic Library Online (Scielo), Brazilian Bibliography of Dentistry (BBO) and Medical Literature Analysis and Retrievel System Online (Medline), in Portuguese and English. The Boolean marker “AND” was used among the descriptors contained in the Health Sciences Descriptors (DeCS) website, namely: Composite resins, polymerization shrinkage, Bulk fill composite resins. Articles that did not meet the objectives of the study were excluded. Results: In view of the review, 13 articles were selected, which indicated lower polymerization contraction of bulkfill resins, requiring a more judicious insertion technique to obtain restorative success. Conclusion: In view of this, it is concluded that composite resins of bulk fill type, due to their greater viscosity and flow in their composition, have similar or less polymerization contraction than conventional composite resins.